The school experience of Malay adolescent with conduct issues - Daud, Mohd Najmi; Coombes, Leigh; Venkateswar, Sita; Ross, Kirsty; Rosnon, Mohd Roslan (Human Resource Management Academic Research Society, 2019)
This research is designed to explore how Malay adolescents who have been identified with conduct issues understand their school experiences. This research is a qualitative research, which utilized Interpretative Phenomenological Analysis (IPA) as an analysis method. Ten participants were recruited from a rehabilitation center for young offenders in Malaysia. Each participant completed at least two semi-structured interviews. The interviews were digitally recorded, transcribed, translated and analyzed for content. Through the emerging themes namely subject-oriented, issues pertaining to English as a medium of instruction, the nature of the school, inconsistency between personal interests and what the school has to offer, experiencing teaching and learning issues and individual differences related to school experiences, analysis suggest that participants felt disadvantaged by the school system. They felt that the education policies and school environment were irrelevant and unresponsive to their capabilities, needs, desires and interests. Thus, apart from benefiting people who work closely with these adolescents, this research provides the voice for the participant so that they feel heard.